Enhanced strength-ductility synergy and activation of non-basal slip in as-extruded Mg–Zn–Ca alloy via heterostructure - Hongfei Zhang; Yutian Ding; Ruimin Li; Yubi Gao (Journal of Materials Research and Technology, 2024)
The relationship between the heterogeneous grain structure and mechanical properties is an emerging aspect of the effort to expand the applications of Mg alloy. In this study, heterostructured Mg alloy, comprising elongated and fine equiaxed grains, was fabricated through a simple hot-extrusion process with extrusion temperature of 320 °C. This resulted in a yield strength (YS) of approximately 192 MPa and excellent elongation of approximately 20.4 %. When compared to the alloy extruded at 360 °C, which had a homogenized structure, the increased YS in the 320 °C extruded alloy was primarily attributed to hetero-deformation-induced (HDI) strengthening. The inclusion of Zn and Ca, along with stress concentration, promoted active <c+a> slips, thereby enhancing the ductility of the alloy extruded at 320 °C. This endeavour provides an inspiring strategy for improving the YS of Mg–Zn–Ca alloys without significantly compromising ductility.